EFEKTIVITAS REVITALISASI KADER DALAM PENINGKATAN PENGETAHUAN DAN KETERAMPILAN EDUKASI PADA KELAS IBU HAMIL - Chabibah, Nur; Kristiyanti, Rini; yani, Fitri (Siklus : Journal Research Midwifery Politeknik Tegal, 2023)
Breast milk is one of the needs of newborns that must be met by mothers until the baby is six months old. Exclusive breastfeeding is equivalent to saving 804,000 children from death in 2011. The success of breastfeeding mothers to continue breastfeeding their babies is largely determined by the support from their husbands, families, health workers, the community and the work environment. Breastfeeding support provided by health workers and people around the mother both during pregnancy and after giving birth is very helpful for mothers to breastfeed their children as soon and as long as possible. The objective of this study were to analyze the effectiveness of community heatlh volunteer revitalization for increasing the knowledge and skills providing education in the Prenatal class.This study used a quasi-experimental design with a one group pre-test and post-test design approach. The revitalization was given as a refreshing for community heatlh volunteer  which was carried out in two days with an agenda of one day of material reflection and one day of refreshing educational practices about exclusive breastfeeding, correct breastfeeding techniques, and how to express breast milk. The population of this study were community heatlh volunteer in eight villages in the Kedungwuni II Health Center Work Area, Pekalongan Regency. The sampling technique was using purposive sampling, the research subjects were 39 cadres. Data analysis used paired t-test with 95% CI.There are differences in the knowledge of cadres before being given training and after being given training. The average value of cadres' knowledge about exclusive breastfeeding before being given training was 89.74, increasing to 92 after being given exclusive breastfeeding training for two days. The revitalization of community heatlh volunteer can increase knowledge about lactation management significantly with ρ value: 0.024.and improve the skills of cadres in providing education about lactation management with ρ value: 0.003.